Maternal Knowledge, Attitudes, and Practices Concerning Interpregnancy Interval - Ahlers-Schmidt, Carolyn R.; Woods, Nikki Keene; Bradshaw, Danielle; Rempel, Anna; Engel, Matt; Benton, Mary (Kansas Journal of Medicine, 2018)
Introduction. Few studies have examined maternal intentions and practices related to interpregnancy interval (IPI). IPI less than 18 months has been linked to increased preterm birth and infant mortality. This manuscript reports on a cross-sectional survey of mothers conducted to understand maternal knowledge, attitudes, and practice of IPI in Sedgwick County, Kansas. Methods. New and expectant mothers and mothers of neonatal infant care unit (NICU) graduates (n = 125) were surveyed regarding the issues surrounding IPI. Front desk staff handed out self-administered surveys, which were returned to a nurse upon completion. NICU participants were emailed a link to the survey hosted on SurveyMonkey ®. Results. Fewer than 30% of mothers reported previously receiving information about IPI from any source. When asked about risks associated with IPI, women frequently (n = 58, 45%) identified increased risk for birth outcomes with no known association with short IPI. Findings regarding maternal attitudes surrounding optimal IPI were mixed with many mothers defining ideal IPI as less than 18 months (n = 52, 42%), while broadly reporting they believed that a woman’s body needs time to heal between pregnancies. Respondents from the NICU sample generally reported shorter optimal IPI values than the other participants. When IPI was estimated from participants’ past pregnancies, half of IPIs were less than 18 months. Mothers reported they favored healthcare providers as a source for IPI education. Faceto- face discussions or printed materials were the preferred modes of education. Conclusions. Women were aware of the need for spacing between pregnancies, however, that knowledge was unassociated with past behavior. These findings should be taken into consideration when formulating future interventions. Kans J Med 2018;11(4):86-90.